Joint NTAV/SPA 2012 Conference Lodz University of Technology Poland, September 27 – 29, 2012 - STRUMIŁŁO, Paweł (Archives of Acoustics, 2012)
The NTAV/SPA 2012 conference was held on 27–29th September 2012 and was organized by the Institute of Electronics, Lodz University of Technology (www.eletel.p.lodz.pl) with the support of the IEEE Polish Section Region 8, Polish Section of the Audio Engineering Society, Department of Acoustics, Wroclaw University of Technology and the Division of Signal Processing and Electronic Systems, Poznan University of Technology. This scientific event has joined two successful series of conferences: the New Trends in Audio and Video (NTAV) conference – organized biannually since 1994 by major technical universities in Poland and the IEEE Signal Processing: Algorithms, Architectures, Arrangements, and Applications (SPA) conference – first held in 1993 and then organized yearly since 1999 by the Poznan University of Technology. The scope of the NTAV/SPA 2012 joint conference has covered a broad range of topics related to audio, image and video processing, digital signal processing theory, and numerous practical applications including human-computer interaction systems and medicine (see the conference webpage at www.ntavspa.pl for a conference programme). Fourteen of the accepted submissions were devoted to audio processing, analysis or acoustics. They can be grouped into the following thematic fields: processing and coding techniques of audio signals (including cepstral analysis and time-scale decomposition), music modeling and matching, sound and melody recognition, multimedia, acoustics and psychoacousitcs. We hope that the provided list of abstracts will encourage the readers of the Archives of Acoustics to probe further into the presented new trends of audio processing and analysis. On behalf of the conference co-organizers the Polish Section of the Audio Engineering Society and the Polish Association of Theoretical and Applied Electrotechnics the NTAVSPA 2012 Organizing Committee acknowledges the financial support of the Ministry of Science and Higher Education.